(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the clinical and paraclinical characteristics of pregnant women with preeclampsia at Thai Nguyen Central Hospital from January 1, 2022 to December 31, 2024. Subjects and research methods: Cross-sectional, retrospective descriptive research method on 96 patients with medical records diagnosed with preeclampsia who were treated and delivered at Thai Nguyen Central Hospital from January 1, 2022 to December 31, 2024. Results: Cross-sectional study describing clinical and paraclinical characteristics of 96 pregnant women diagnosed with preeclampsia at Thai Nguyen Central Hospital from January 1, 2022 to December 31, 2024. The results showed that the average age of pregnant women was 30.67 ± 6.7, the group of pregnant women aged 20-34 years old accounted for the majority (66.7%). Among the study, 53.1% of patients were diagnosed with severe preeclampsia. Edema was the most common clinical symptom (85.4%). Headache accounted for 45.8%, there were 2 cases of visual disturbances and 3 cases of epigastric-right hypochondriac pain. There were 37.5% of cases with grade 2 hypertension and 36.5% of cases with grade 3 hypertension. Most cases had proteinuria of 500 - 1000 mg/dl. The rates of thrombocytopenia, increased liver enzymes, and increased blood creatinine were 16.7%, 10.4%, and 7.3%, respectively. The difference in testing between the preeclampsia and severe preeclampsia groups was statistically significant (p<0.05). Conclusion: Severe preeclampsia accounted for a fairly high rate.